Cellular alterations and crosstalk in the osteochondral joint in osteoarthritis and promising therapeutic strategies. (2nd November 2021) - Jiang, Ai; Xu, Peng; Sun, Shang; Zhao, Zhenda; Tan, Qizhao; Li, Weishi; Song, Chunli; Leng, Huijie
ABSTRACT: Osteoarthritis (OA) is a joint disorder involving cartilage degeneration and subchondral bone sclerosis. The bone-cartilage interface is implicated in OA pathogenesis due to its susceptibility to mechanical and biological factors. The crosstalk between cartilage and the underlying subchondral bone is elevated in OA due to multiple factors, such as increased vascularization, porosity, microcracks and fissures. Changes in the osteochondral joint are traceable to alterations in chondrocytes and bone cells (osteoblasts, osteocytes and osteoclasts). The phenotypes of these cells can change with the progression of OA. Aberrant intercellular communications among bone cell-bone cell and bone cell-chondrocyte are of great importance and might be the factors promoting OA development. An appreciation of cellular phenotypic changes in OA and the mechanisms by which these cells communicate would be expected to lead to the development of targeted drugs with fewer side effects.